P847 A pilot trial on the effect of a fibre-enriched nutritional supplement on the gut microbiota of stricturing Crohn's disease patients. (15th January 2020) - Herrera De Guise, C M; Varela, E; Ibarz, A; Burgos, R; Cardenas, G; Luis Fernando, M; Robles, V; Borruel, N; Guarner Aguilar, F; Casellas, F
Abstract: Background: Diet is a potential factor that could influence the pathogenesis and activity of Inflammatory Bowel Disease(IBD). Soluble fibre is the best way to generate short-chain fatty acids such as butyrate, which has anti-inflammatory effects. Around 1/3 of Crohn's disease (CD) patients will present with stricturing disease, most frequently in the terminal ileum. These patients often follow a very low-residue diet. CD patients present significant changes in the structure of their microbiota with a decreased prevalence of butyrate-producing bacteria such as Clostridiales species, particularly Faecalibacterium prausnitzii. Depletion of F. prausnitzii might be further enhanced in patients with a very low-residue diet. The aim of this study was to evaluate the effect of a nutritional supplement enriched with soluble fibre on the abundance of F. prausnitzii in stricturing CD. Methods: We performed a single arm, pilot trial in CD patients with ileal stricturing disease who followed a very low-residue diet as assessed by a dietician. The fibre-enriched nutritional supplement (reg#26.06141/BA-72556) consisted of a 200ml vanilla-flavoured shake that included 3.4 gr of soluble fibre, omega-3 and oleic fatty acids. Patients received 2 supplements per day for 6 weeks, and were followed for 6 months. We obtained frozen faecal samples at time-points 0, 3, 6, 12 and 24 weeks. Total bacteria and F. prausnitzii counts were assessed by qPCR. Weight, BMI, CD activity index (CDAI), CRP, fatty acids, urine F2-isoprostanes and faecal calprotectin were also determined. Tolerance, palatability and acceptability of the supplement were assessed with validated questionnaires at weeks 3 and 6. Results: Ten patients were included in the study with a median age of 38 [36–50] years, 60% were male, median BMI 25.2 [24.3–28.4] and 40% were current smokers. Six patients completed the 6 weeks of the supplement. Two patients did not receive the supplement because they underwent ileocecal resection, 1 patient was lost to follow-up and 1 patient dropped-out early because of poor palatability of the supplement. At baseline, all patients had F. prausnitzii levels below 10 9 CFU/g (median 2.02 × 10 6 ). Supplement intake did not significantly increase F. prausnitzii levels ( p = 0.73) and had no effect on CDAI, CRP, urine F2-isoprostanes or faecal calprotectin. Most usual complaints associated with the supplement were abdominal bloating and flatulence. Conclusion: CD patients with structuring disease and who follow a very low-residue diet have a markedly reduced abundance of F. prausnitzii . Intake of a 6.8 g/day fibre-enriched nutritional supplement was unable to significantly increase F. prausnitzii abundance in these patients. Fibre supplement was not associated with adverse events.